2012
DOI: 10.1089/pho.2012.3306
|View full text |Cite
|
Sign up to set email alerts
|

Skin Penetration Time-Profiles for Continuous 810 nm and Superpulsed 904 nm Lasers in a Rat Model

Abstract: Objective: The purpose of this study was to investigate the rat skin penetration abilities of two commercially available low-level laser therapy (LLLT) devices during 150 sec of irradiation. Background data: Effective LLLT irradiation typically lasts from 20 sec up to a few minutes, but the LLLT time-profiles for skin penetration of light energy have not yet been investigated. Materials and methods: Sixty-two skin flaps overlaying rat's gastrocnemius muscles were harvested and immediately irradiated with LLLT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 29 publications
4
34
0
2
Order By: Relevance
“…It has been further revealed that LLLT in PW mode can better penetrate through the melanin and other skin barriers, supporting the hypotheses that pulsing is beneficial in reaching deep target tissue and organs [25]. Some recent studies have demonstrated that PW mode is advantageous over the CW mode, particularly, in the context of repair of deep tissue injuries and stroke management [2527]. Ilic et al, reported that pulsed light produced no neurological or tissue damage, whereas an equal power density delivered by CW caused marked neurological deficits [28].…”
Section: Introductionmentioning
confidence: 80%
“…It has been further revealed that LLLT in PW mode can better penetrate through the melanin and other skin barriers, supporting the hypotheses that pulsing is beneficial in reaching deep target tissue and organs [25]. Some recent studies have demonstrated that PW mode is advantageous over the CW mode, particularly, in the context of repair of deep tissue injuries and stroke management [2527]. Ilic et al, reported that pulsed light produced no neurological or tissue damage, whereas an equal power density delivered by CW caused marked neurological deficits [28].…”
Section: Introductionmentioning
confidence: 80%
“…The penetrability of certain wavelengths varies in different tissues. According to Joensen et al 36 , the amount of penetrating light energy is 20% for a wavelength of 810 nm and 58% for a wavelength of 904 nm. King et al 37 found that the penetration of laser irradiation into skin is limited to a few millimeters.…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, the use of an infrared laser is justified, because of its greater depth of penetration. 26,27 The relationships between basic LLLT parameters and their relationships to wound healing are still not fully understood; therefore, the optimal wound type-specific treatment has not yet been determined. In an open wound model, we have previously shown that LLLT at wavelengths 635 and 670 nm was more effective when higher intensity was combined with shorter wavelength and/or lower intensity was combined with higher wavelength.…”
Section: Discussionmentioning
confidence: 99%